College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 9 - Section 9.3 - Geometric Sequences; Geometric Series - 9.3 Assess Your Understanding - Page 664: 43


$2\displaystyle \left[1-\left(\frac{2}{3}\right)^{n}\right]$

Work Step by Step

$\displaystyle \sum_{k=1}^{n}\left(\frac{2}{3}\right)^{k}=\sum_{k=1}^{n}\frac{2}{3}\left(\frac{2}{3}\right)^{k-1}$ Apply THEOREM: Sum of the First $n$ Terms of a Geometric Sequence $S_{n}=\displaystyle \sum_{k=1}^{n}a_{1}r^{k-1}=a_{1}\cdot\frac{1-r^{n}}{1-r},\quad r\neq 0,1$ Here, $a_{1}=\displaystyle \frac{2}{3}, r=\frac{2}{3}$ $S_{n}=a_{1}\displaystyle \left(\frac{1-r^{n}}{1-r}\right)=\frac{2}{3}\cdot\frac{1-\left(\frac{2}{3}\right)^{n}}{1-\frac{2}{3}}$ $=\displaystyle \frac{2}{3}\cdot\frac{1-\left(\frac{2}{3}\right)^{n}}{\frac{1}{3}}$ $=2\displaystyle \left[1-\left(\frac{2}{3}\right)^{n}\right]$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.